Arab resistance in the diaspora: Comparing the Saudi dissident and the Egyptian whistleblower. (1st April 2020) - Khamis, Sahar; Fowler, Randall
While much research on Arab and Muslim diasporas in the West focuses on the War(s) on Terror, in this article, we explore how two particular diasporic groups, Egyptian and Saudi activists, work to shape public perceptions of the authoritarian regimes in their countries of origin. Contextualizing the efforts of these activists in the post-Arab Spring political and mediated environments, we investigate how these political exiles employ communication to disrupt, expose and resist the resurgent authoritarianism taking root in their countries of origin. Using a comparative framework, we analyse the discourse of two prominent activists, Mohamed Ali and Omar Abdelaziz, to illustrate the larger dynamics of online cyberactivism amongst these diasporic groups. Critically, we argue, the differences in these two activists' communicative practices demonstrate how ostensibly similar resistance movements may lead to disparate political outcomes, as their calls for change diverge when it comes to issues of reform versus revolution. In doing so, we seek to complicate overly simplistic understandings of Arab anti-authoritarian resistance taking place online in the post-Arab Spring era.